Emergency in pediatric and adolescent psychiatry. Note taking for the primary health assistance. - Zenaida María Sáez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
The psyquiatric emergences in children and adolescents are usually manifested as alterations of the feelings, behavior or in the school efficiency and its origin is found in the physical tensions, contradictions in the breeding, marital conflicts, bad interpersonal relationships, negligence, loss of the significant model at home, etc. It is important to address that there is no direct relationship between the causal factor and the onset of the symptoms. This largely depends on variables such as temperament, levels of development, nature and duration of the stress, past experience and family capacity/ability of the family to get adapted to new situations. Parents frequently come to visit General Comprehensive doctor because they are worried about their children´s behaviors, i.e.; if they are normal or require certain intervention. In the current review we make reference to the psychosocial issues that may bring about psychopathological manifestations which need a timely intervention. Otherwise, there is a risk for the physical integrity of the kid, adolescent or another people which may result into a remarkable complications and suffering for the patients or their relatives. We are going to make reference to the abuse of some substances, adoption, nervous anorexia, suicide attempt, infant abuse, fire provocation and mourning reaction. We are making emphasis on the clinical assessment of the risk factors which contribute to the appearance of these issues and the management in the primary level of assistance to prevent further complications.